Establishment and characterization of melanoma patient-derived xenograft models for preclinical evaluation of novel therapeutics. Issue 6 (December 2018) - Yan, Junya; Wu, Xiaowen; Yu, Jiayi; Ma, Meng; Yu, Huan; Xu, Tianxiao; Tang, Huan; Xu, Longwen; Dai, Jie; Si, Lu; Chi, Zhihong; Sheng, Xinan; et al.
Abstract : Patient-derived xenograft (PDX) models mostly retain the histological and genetic features of their donor tumors, which have been used for investigating various types of cancer. However, PDX models for melanoma, especially acral melanoma, are reported occasionally. We aimed to establish a large panel of melanoma PDX models representing the predominant Asian melanomas. Ninety-three fresh melanoma samples were implanted subcutaneously into nonobese diabetic/severe combined immunodeficiency mice. The histological and genetic characteristics were analyzed in both patient tumors and PDX models using immunohistochemistry, PCR amplification, and Sanger sequencing. Furthermore, the sensitivities of PDX models harboring distinct mutation profiles to binimetinib (a MEK inhibitor), vemubrafenib (a BRAF inhibitor), and imatinib (a KIT inhibitor) were also evaluated. Twenty-five PDX models were established successfully [25/93 (26.9%)] and passaged to maintain tumors in vivo . Clinical stage and origin of tumor sample were correlated with successful establishment rates ( P =0.008 and <0.001, respectively). The histological (expression of NRAS, P16, and RB) and genetic (mutation status of NRAS, BRAF, and KIT ) characteristics were stably maintained from patient tumors to PDX models. Targeted drugs could inhibit the tumor growth of PDX models harboring the corresponding target gene mutations. These PDX models constitute a pharmacological platform, enabling personalized development of therapeutic strategies for Asian melanomas. Abstract : Supplemental Digital Content is available in the text.